HEALTH IMPACT OF DEFORESTATION ON RURAL COMMUNITIES IN SOUTHERN KADUNA SENATORIAL DISTRICT - Shekari Kura Gandu, Jacob (African Journal of Social and Behavioural Sciences, 2025)
Forests significantly contribute to human health. Deforestation of these forests can have notable direct and indirect effects on human well-being. Deforestation greatly disrupts the ecological balance, leading to the spread of disease pathogens and their carriers in rural communities in the Southern Senatorial District of Kaduna State. This study examines the health impact of deforestation in the area, with a specific focus on adverse health outcomes. It explores and describes health-related perspectives linked to deforestation in rural communities. The research used both qualitative and quantitative social research methods for data collection. Questionnaires were randomly distributed to 600 respondents across four selected Local Government Areas, and ten key informants were also interviewed. Data analysis incorporated descriptive statistical techniques for the quantitative data and content analysis for the qualitative data. The results showed a high prevalence of malaria among residents, which is indirectly associated with deforestation as a result of the rise in temperatures, which, over time, enhances mosquito breeding and leads to more cases of malaria. The study recommends that relevant authorities, like the State Government, in collaboration with the LGAs, educate communities on the severity of deforestation on human health. Additionally, relevant forest control agencies must understand the social perceptions of the people to aid in addressing complex social-environmental challenges and support policymakers in adopting more sustainable and inclusive forest management practices. Based on these findings, the study advocates for the proper management and intensification of existing agriculture rather than expanding into untouched lands.